2011
DOI: 10.1111/j.1365-2133.2011.10507.x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the immune system in skin cancer

Abstract: Over the past several decades, there has been increasing interest in understanding the roles of the immune system in the development and progression of cancer. The importance of the immune system in human skin cancer has been long recognised based primarily upon the increased incidence of skin cancers in organ transplant recipients and mechanisms of ultraviolet light-mediated immunomodulation. In this review, we integrate multiple lines of evidence highlighting the roles of the immune system in skin cancer. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
153
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(159 citation statements)
references
References 244 publications
(220 reference statements)
0
153
1
5
Order By: Relevance
“…In these studies, the ratio was suggested as a valuable tool for the prediction of development and aggressive growth of transplant associated SCC. Renal transplant recipients showed more increased incidence for SCC than BCC [17]. Previous studies have shown that MHC class I expression and CD8 positive T cell infiltration were significantly decreased in BCC compared to SCC [3,23].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In these studies, the ratio was suggested as a valuable tool for the prediction of development and aggressive growth of transplant associated SCC. Renal transplant recipients showed more increased incidence for SCC than BCC [17]. Previous studies have shown that MHC class I expression and CD8 positive T cell infiltration were significantly decreased in BCC compared to SCC [3,23].…”
Section: Introductionmentioning
confidence: 86%
“…Ultraviolet radiation is closely implicated in the carcinogenesis of squmaous cell carcinoma (SCC) and basal cell carcinoma (BCC) because it induces DNA mutations and immunosuppression [1,17]. Both tumors frequently occur in organ transplant recipients (OTR), in which their occurrences are also correlated with the level of immunosuppression [8].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer immunosurveillance refers to the monitoring function of the immune system in cancer development. There are studies that have demonstrated that the immune system can recognize and eliminate aberrant cancer cells arising within the human body [51][52][53][54][55][56]. Thus, the interaction between cancer and the immune system plays a pivotal role in cancer development.…”
Section: Interactions Between Cancer and The Immune Systemmentioning
confidence: 99%
“…14,35 Although mortality from NMSC is rare in the immunocompetent population, this malignancy represents a considerable burden on the health-care system, particularly when considering immunosuppressed patients. 7 It is estimated that up to 40% of OTR will develop skin cancers, 90% of which are BCC and SCC, within the first 10 y of transplantation, and up to 80% will do so after 20 y 36 Additionally, skin malignancies are more aggressive in OTRs, with only 56% of 3-year diseasespecific survival. 37 Therefore, a prophylactic strategy that could prevent or reduce the impact of these skin manifestations is much needed.…”
Section: Introductionmentioning
confidence: 99%